Where have you been? selected essays - Hofmann, Michael 1957- (Faber & Faber, 2015)
This book offers a new selection of essays from Michael Hofmann - one of our most exceptional critics of contemporary literature. "Superb and invigorating." (Nicholas Shakespeare, Daily Telegraph). In these thirty essays, Hofmann brings his signature wit and sustained critical mastery to a poetic, penetrating, and candid discussion of the writers and artists of the last hundred years. Here are the indispensable poets without which contemporary poetry would be unimaginable - Elizabeth Bishop, Robert Lowell, and the man he calls the greatest English poet since Shakespeare, Ted Hughes. But he also illumines the despair of John Berryman and the antics of poetry's bogeyman, Frederick Seidel. In essays on art that are themselves works of art, Hofmann's agile and brilliant mind explores a panoply of subjects from the mastery of translation to the best day job for a poet. Where Have You Been? It is an unmissable journey with literature's most irresistible flaneur. At the same time, it is a story of love between a reader and his treasured books.